2010
DOI: 10.1093/tropej/fmq047
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Prediction Score for Nasal CPAP Failure in Pre-term VLBW Neonates with Early Onset Respiratory Distress

Abstract: We prospectively observed 62 pre-term very low birth weight neonates initiated on nasal continuous positive airway pressure (CPAP) for respiratory distress in the first 24 h of life to devise a clinical score for predicting its failure. CPAP was administered using short binasal prongs with conventional ventilators. On multivariate analysis, we found three variables-gestation <28 weeks [adjusted odds ratio (OR) 6.5; 95% confidence interval (CI) 1.5-28.3], pre-term premature rupture of membranes [adjusted OR 5.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 9 publications
5
32
4
1
Order By: Relevance
“…Another study in which infants on CPAP were intubated at an FiO 2 of 0.6 found that a lower intubation threshold would not have altered the numbers of infants intubated, but only delayed the time of intubation [9]. Despite the long documented observation of better oxygenation with higher airway pressures on CPAP [20], addition of CPAP level into the predictive modelling in the present study, either alone or as a product with FiO 2 [11], only marginally improved the goodness of fit.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Another study in which infants on CPAP were intubated at an FiO 2 of 0.6 found that a lower intubation threshold would not have altered the numbers of infants intubated, but only delayed the time of intubation [9]. Despite the long documented observation of better oxygenation with higher airway pressures on CPAP [20], addition of CPAP level into the predictive modelling in the present study, either alone or as a product with FiO 2 [11], only marginally improved the goodness of fit.…”
Section: Discussionmentioning
confidence: 82%
“…The respiratory course for all infants managed initially on CPAP was defined from the intensive care charts. Data recorded included highest FiO 2 (sustained for at least 15 min), CPAP pressure and CPAP-FiO 2 product (= CPAP level in cm H 2 O × FiO 2 ) [11] in the first 2 h (25-28 weeks) or first 6 h (29-32 weeks), as well as highest PCO 2 in the first 6 h. For those failing CPAP, defined as the need for intubation before 72 h [7], the most recent physiological parameters prior to intubation were documented, and the radiological severity of RDS was categorised by one of the authors as mild, moderate or severe [12]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our FiO 2 (≥0.4) may be considered by some to be too low and result in more infants being classified as failing CPAP than if higher FiO 2 was used. Several studies have used FiO 2 >0.6 [2,3,4,18]. CPAP levels used at RWH are higher than those used by other groups [3,5] and these infants might have met CPAP failure criteria at other institutions.…”
Section: Discussionmentioning
confidence: 99%
“…51,68,69 Not surprisingly, both an increasing oxygen requirement (>40%) in the first hours of life and an increasing CPAP requirement (>6 cm H 2 O) predict failure. 51,[68][69][70] However, as most units include these factors as criteria for intubation, this association is necessarily confounded as a predictor of failure. A recent small study has shown that low tidal volume breaths, lower peak inspiratory flows, and increased oxygen requirement immediately after delivery can predict CPAP failure and deserves further study.…”
Section: The Benefit Of Surfactant Without Mechanical Ventilation: Inmentioning
confidence: 99%